2007
DOI: 10.1111/j.1399-0039.2007.00907.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of CD94/NKG2A, CD94/NKG2C, and its ligand HLA‐E polymorphisms with Behcet’s disease

Abstract: Inhibitory CD94/NKG2A and activating CD94/NKG2C receptors are expressed on natural killer, CD4, and CD8 T cells and recognize human leukocyte antigen (HLA)-E, resulting in the modulation of cytotoxic activity and cytokine production. An imbalance in cytotoxic activity and cytokine production has been implicated in Behcet's disease (BD). The results of this study showed that the NKG2A c.-4258*C, c.338-90*G, and CD94 c.-134*T alleles (P ¼ 0.015, OR ¼ 0.8; P < 0.0001, OR ¼ 0.5; and P ¼ 0.034, OR ¼ 0.8, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…The role of the HLA-E in the development of autoimmunity is supported by several studies. The HLA-E*01:03/ 01:03 genotype has been associated with increased risk of Behc¸et's disease (BD) [18]. Moreover, this genotype was found to be a risk factor for pemphigus vulgaris (PV) development [20].…”
Section: Discussionmentioning
confidence: 99%
“…The role of the HLA-E in the development of autoimmunity is supported by several studies. The HLA-E*01:03/ 01:03 genotype has been associated with increased risk of Behc¸et's disease (BD) [18]. Moreover, this genotype was found to be a risk factor for pemphigus vulgaris (PV) development [20].…”
Section: Discussionmentioning
confidence: 99%
“…Though no variation was detected in coding regions of CD94 gene, it has SNP at position c. (Hikami et al 2003;Park et al 2008;Seo et al 2007).…”
Section: Organization and Expression Of Genes Within The Cd94/nkg2 CLmentioning
confidence: 99%
“…The NKG2A SNPs c. -4258*C and c. 338-90*G, as well as the CD94 SNP c. -134*T were connected with decreased risk of Behçet's disease (Seo et al 2007). Moreover, the NKG2A c. 338-90*AA, NKG2C 102 Ser/ Ser, and NKG2D 72*Ala/Ala were significantly correlated Activating and inhibitory signal transduction and regulation in NK cells or CTLs.…”
Section: Organization and Expression Of Genes Within The Cd94/nkg2 CLmentioning
confidence: 99%
“…HLA-E rs1264457 dimorphism at position 107 resulting in differential expression of HLA-E (E*01:01 and E*01:03) alleles on cell surface is reported to have important clinical implications for immune mediated disorders through its role as a regulatory molecule and its interaction with NK cell receptors. 5,15,16,25 There is paucity of data on the role of HLA-E polymorphism in inflammatory arthritides. The only study published till date is from Sardinia, which reported its low expressor variant (HLA-E*01:01) to be associated with ankylosing spondylitis.…”
Section: Discussionmentioning
confidence: 98%